Imaging the 2016 Mw 7.8 Kaikoura, New Zealand, earthquake with teleseismic P waves: A cascading rupture across multiple faults. Issue 10 (21st May 2017) - Zhang, Hao; Koper, Keith D.; Pankow, Kristine; Ge, Zengxi
Abstract: The 13 November 2016 M w 7.8 Kaikoura, New Zealand, earthquake was investigated using teleseismic P waves. Backprojection of high‐frequency P waves from two regional arrays shows unilateral rupture of at least two southwest‐northeast striking faults with an average rupture speed of 1.4–1.6 km/s and total duration of 100 s. Guided by these backprojection results, 33 globally distributed low‐frequency P waves were inverted for a finite fault model (FFM) of slip. The FFM showed evidence of several subevents; however, it lacked significant moment release near the epicenter, where a large burst of high‐frequency energy was observed. A local strong‐motion network recorded strong shaking near the epicenter; hence, for this earthquake the distribution of backprojection energy is superior to the FFM as a guide of strong shaking. For future large earthquakes that occur in regions without strong‐motion networks, initial shaking estimates could benefit from backprojection constraints. Key Points: Unilateral rupture to the northeast with an average velocity of 1.4–1.6 km/s and total duration of 100 s Multiple faults within the Marlborough system were activated during the rupture Peak ground acceleration near the source is better correlated with areas of short‐period energy release than with areas of large slip